Optimization of Waiting Time at Drive Thru Fast Food Restaurant using Queuing Model - Zulkarnain, Nuru Ain Athirah; Azila Md Sudin (Enhanced Knowledge in Sciences and Technology, 2024)
Fast food supply is in high demand, particularly in a society where people are constantly working. Previous studies have demonstrated that the majority of working populations spend insufficient time at home. As a result, they are requesting fast food or other appropriate products that fit their lifestyle. The mathematical theory that focuses on waiting lines is the source of waiting time theory, also known as queuing theory. This theory is typically applied to customer wait times in lines in the service industry. The goal of the research is to find the best waiting line model for cutting down on customer wait times and to identify the reasons why customers wait in line for extended periods of time. Single queue theory and multiple queue theory are the two categories of queuing theory. In this study, the primary tool for gathering data will be descriptive analysis, and single queue theory will be utilized to collect data. The study was only carried out during the lunch hour, or peak hour, which is from 12 to 2 p.m. at McDonald’s Kok Lanas for five days. The gathered data will be examined using Excel. Additionally, the McDonald's restaurant will use the observation and simulation model approach to cut down on customer wait times.